KARAKTERISASI KAOLIN KAB.BARRU SEBAGAI BAHAN DASAR KERAMIK - Hamzah, Muhammad Sadat (MEKTEK, 2005)
Study conducted by represent the study of early storeylevel of ability of exploiting or kaolin potency of an area which is later;then actedÂ  . in this penelitiaan on the market idea to exploit the existing resource the core important regional industrial dig materials of sulawesi south . Ceramic in this time experience of the fast progress where materials of the core important kaolin but to know the ability which is consisted inÂ  it hence there is its character standard . hence in this examination combine the conventional analysis and carakterisasi to kaolin materials done by perception with the instrument of like X-RD, SEM / EDAX And DTA. This test is conducted for to prove the compiler rate . structure. and ability and ability which is consisted in in its material is then clarified by optimalisasi of according to obtained result value